3′-Sialyllactose as an inhibitor of p65 phosphorylation ameliorates the progression of experimental rheumatoid arthritis - Kang, Li Jung; Kwon, Eun Soo; Lee, Kwang Min; Cho, Chanmi; Lee, Jae In; Ryu, Young Bae; Youm, Tae Hyun; Jeon, Jimin; Cho, Mi Ra; Jeong, Seon Yong; Lee, Sang Rae; Kim, Wook; et al. (British Journal of Pharmacology, 2018)
Background and Purpose: 3′-Sialyllactose (3′-SL) is a safe compound that is present in high levels in human milk. Although it has anti-inflammatory properties and supports immune homeostasis, its effect on collagen-induced arthritis (CIA) is unknown. In this study, we investigated the prophylactic and therapeutic effect of 3′-SL on the progression of rheumatoid arthritis (RA) in in vitro and in vivo models. Experimental Approach: The anti-arthritic effect of 3′-SL was analysed with fibroblast-like synoviocytes in vitro and an in vivo mouse model of CIA. RT-PCR, Western blotting and ELISA were performed to evaluate its effects in vitro. Histological analysis of ankle and knee joints of mice with CIA was performed using immunohistochemistry, as well as safranin-O and haematoxylin staining. Key Results: 3′-SL markedly alleviated the severity of CIA in the mice by reducing paw swelling, clinical scores, incidence rate, serum levels of inflammatory cytokines and autoantibody production. Moreover, 3′-SL reduced synovitis and pannus formation and suppressed cartilage destruction by blocking secretion of chemokines, pro-inflammatory cytokines, matrix metalloproteinases and osteoclastogenesis via NF-κB signalling. Notably, phosphorylation of p65, which is a key protein in the NF-κB signalling pathway, was totally blocked by 3′-SL in the RA models. Conclusions and Implications: 3′-SL ameliorated pathogenesis of CIA by suppressing catabolic factor expression, proliferation of inflammatory immune cells and osteoclastogenesis. These effects were mediated via blockade of the NF-κB signalling pathway. Therefore, 3′-SL exerted prophylactic and therapeutic effects and could be a novel therapeutic agent for the treatment of RA.
Keywords: Animals; Arthritis, Rheumatoid; Cells, Cultured; Male; Mice; Mice, Inbred C57BL; Mice, Inbred DBA; Oligosaccharides; Phosphorylation; Transcription Factor RelA